Influence of thermal oxidation temperature on the microstructure and photoelectrochemical properties of ZnO nanostructures fabricated on the zinc scraps - DEMİRCİ, SELİM (ELSEVIER SCIENCE SA, 2019)
In this paper, zinc oxide (ZnO) nanowires were synthesized by thermal oxidation method of zinc scrap at various temperatures ranging between 400 degrees C and 900 degrees C under air atmosphere. The influence of different temperature on the phase structures, surface morphologies and photoelectrochemical (PEC) properties of ZnO nanowires were investigated. The characterizations were carried out via X-ray diffractometer (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX). The results showed that annealing temperature played a significant role on surface morphology and phase structure. The band gap energy of the ZnO nanowires changed between 3.12 and 3.194 eV. The photoelectrochemical (PEC) study of the ZnO nanowires was investigated in 0.1 M Na2SO4 aqueous solution. The PEC findings represented that the ZnO nanowire annealed at 600 degrees C had 252.2 mu A/cm(2) net photocurrent density which was the best efficiency and at least 10 times higher than that of the lowest one at 1.25 V (vs. V-RHE). Mott-Schottky analysis showed that the ZnO nanowires behaved as n-type semiconductor. ZnO nanowire annealed at 600 degrees C had the highest carrier density value (N-d = 9.03 x 10(23)). Moreover, the charge transfer behavior of the ZnO nanowires was determined by means of electrochemical impedance spectroscopy (EIS) measurements. As a result, this work recommends that the ZnO nanowires could be good candidate on PEC applications. Also, thermal oxidation method is an efficient method for fabrication of ZnO nanowires. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Zn scrap; ZnO nanowires; Thermal oxidation; Photoelectrochemical (PEC); Electrochemical impedance spectroscopy (EIS); ELECTRICAL-PROPERTIES; DOPED ZNO; PHOTOCATALYTIC PROPERTIES; CALCINATION TEMPERATURE; ANNEALING TEMPERATURE; CORROSION-RESISTANCE; SOLAR-CELLS; NANOWIRES; FILMS; SEMICONDUCTOR